Evaluating the Role of Homoeopathic Interventions in the Management of Insomnia: A Systematic Review of Clinical Studies. - Patel, Avinash; Patel, Jignesh; Meena, Shiv Ram; Verma, Anurag; Verma, Alpana; Verma, Shipra (Journal of Neonatal Surgery, 2025)
Background: Insomnia is a widespread sleep disorder with major public-health implications, leading to impaired functioning, mood disturbances, and reduced quality of life¹˒². Conventional therapies such as cognitive behavioural therapy for insomnia (CBT-I) and hypnotic medications are commonly recommended but are often associated with limited adherence, adverse effects, or incomplete response¹˒². This has encouraged interest in complementary and alternative modalities, including homoeopathy³˒⁴. Aim of Review: This review evaluates clinical evidence on homoeopathic interventions for insomnia. Methods: A structured literature search was conducted across databases including PubMed, Scopus, Web of Science, AJOL, and the Cochrane Library using predefined criteria⁵˒⁶˒⁷. Results: Forty-one studies met the inclusion criteria, including randomized controlled trials, observational studies, and case series⁵˒⁶. Some trials reported improvements in sleep onset and quality⁸˒⁵, while others found no significant difference compared to placebo⁶˒⁹. Observational studies showed favourable outcomes but had methodological limitations¹⁰˒¹¹. Conclusion: Homoeopathy may provide benefit as an adjunctive therapy, particularly when individualized¹²˒¹³, but current evidence remains insufficient for firm conclusions⁹˒¹⁴. High-quality trials are required¹⁵˒⁷˒⁴...